Computer-Delivered Cognitive Training and Transcranial Direct Current Stimulation in Patients With HIV-Associated Neurocognitive Disorder: A Randomized Trial - Ownby, Raymond L.; Kim, Jae (Frontiers in Aging Neuroscience, 2021)
Objective: HIV infection is associated with impaired cognition, and as individuals grow older, they may also experience age-related changes in mental abilities. Computer-based cognitive training (CCT) and transcranial direct current stimulation (tDCS) have both shown promise in improving cognition. This study evaluated the acceptability of CCT and tDCS to older adults with HIV-associated neurocognitive disorder, and assessed their impact on reaction time, attention, and psychomotor speed. Methods: In a single-blind randomized study, 46 individuals with HIV-associated mild neurocognitive disorder completed neuropsychological measures and six 20-minute training sessions, receiving (1) CCT with active tDCS; (2) CCT with sham tDCS, or (3) watching educational videos with sham tDCS. Immediately after training and again one month later, participants completed follow-up assessments. Outcomes were evaluated via repeated measures mixed effects models. Results: Participant ratings of the intervention were positive. Effects on reaction time were not significant, but measures of attention and psychomotor speed suggested positive effects of the intervention. Conclusion: Both CCT and tDCS were well accepted by older persons with HIV infection. CCT and tDCS may improve cognitive in affected individuals. Registered at ClinicalTrials.gov (NCT03440840).